Love Of Money And Risk Tolerance On Investment Interest In The Digital Era With The Use Of Fintech As A Moderating Variable - Agus Nur Saputra; Isnaini Anniswati Rosyida; Dewi Kusmayasari (LP2M IAIN Palopo, 2026)
The development of digital technology in the financial sector has significantly influenced people's behavior in conducting investment activities, particularly among university students. The accessibility of investment through financial technology (fintech) platforms enables individuals to invest more easily and efficiently. However, investment interest is not only influenced by technological advancements but also by psychological factors such as love of money and risk tolerance. This study aims to analyze the influence of love of money and risk tolerance on investment interest in the digital era with the utilization of fintech as a moderating variable among accounting students in Lamongan Regency. This research employed a quantitative approach using Structural Equation Modeling based on Partial Least Square (PLS-SEM) analyzed with the SmartPLS application. The results indicate that love of money, risk tolerance, and fintech utilization have a positive and significant effect on investment interest. Furthermore, fintech utilization is proven to moderate the relationship between love of money and investment interest as well as the relationship between risk tolerance and investment interest. These findings suggest that psychological factors and the utilization of financial technology play an important role in increasing students' investment interest in the digital era.